Tratamento Cirúrgico dos Tumores Germinativos do Testículo - Srougi, Miguel (2023)
In this study the authors present a critical appraisal of the role of surgery in the strategy of management of patients with germ cell testicular cancer. Special interest is directed to treatment of the primary tumor and the importance of surgery after chemotherapy in patients with advanced disease. Furthermore, a critical discussion on the role of retroperitoneal lymphadenectomy in patients with nonseminomatous tumors is presented.